Profit Sharing System between Punggawa Mappalele, Punggawa Posasiq, and Sawi in fishing activities in Pambusuang Village, Balanipa District, Polewali Mandar Regency - Muhammad Alwi; Muhammad Adam; Sirajuddin; Firman Saputra Jusri (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
The activity of fishing for the Mandar community is a tradition of their ancestors who were famous as accomplished sailors. The aim of this research is to analyze the system and mechanism of profit sharing agreements between punggawa pappalele, punggawa posasiq and sawi in fishing activities in Pambusuang Village, Balanipa District, Polewali Mandar Regency. The method used in this research is a qualitative descriptive method. Data was obtained through observation, interviews and documentation. Data processing is carried out through the process of data reduction, data presentation, and drawing conclusions. The results of the research reveal that the cooperation agreement between punggawa pappalele, punggawa posasiq, and sawi in Pambusuang Village has been practiced for a long time in accordance with tradition and religion. This contract is a profit sharing agreement that applies in general and has been passed down from generation to generation, so that it has become a custom or unwritten agreement among the Pambusuang fishing community. There are differences in the distribution of ratios for fish catches, this depends on the method, method or equipment used to catch fish.